Concurrent Graves' Disease and TSH Secreting Pituitary Adenoma Presenting Suppressed Thyrotropin Levels: A Case Report and Review of the Literature - Fu, Jinrong; Wu, Anhua; Wang, Xiaoli; Guan, Haixia (Frontiers in Endocrinology, 2020)
Background: Thyroid stimulating hormone (TSH) secreting pituitary adenoma (TSHoma) is a rare cause of hyperthyroidism. To date there have been only ten cases reporting the coexistence of TSHoma with Graves’ disease (GD). The diagnosis and management for such hyperthyroidism due to both etiologies remain challenging. Case Report: A 55-year-old Chinese female presented with signs and symptoms of thyrotoxicosis. Thyroid function tests showed elevated thyroid hormones and mildly suppressed TSH values. Her anti-thyrotropin receptor antibody (TRAb) was positive. Octreotide suppression test successfully decreased her TSH. Magnetic resonance imaging showed a pituitary macroadenoma. She underwent endoscopic trans-sphenoidal resection and surgical pathology confirmed a TSH producing pituitary adenoma. Methimazole was prescribed after surgery and her clinical course was monitored. Conclusions: Here we report a case of a 55-year-old female with TSHoma and Graves’ disease whose TSH level was mildly suppressed. This case emphasizes the importance of thoroughly evaluating the thyroid function test during the diagnosis of hyperthyroidism. It also highlights the challenges in the diagnosis and treatment of this rare condition.